VUNA: A Prototype for Organisation and Retrieval of Newspaper Items (Bangladesh Journal of Library and Information Science, 2012)
This is the age of information explosion. A massive quantity of information is being generated, a large portion of which is found in newspapers. It is posing a unique challenge for information managers for processing information and providing required information to information seekers. This article discusses a newspaper information retrieval system named Vidyasagar University News Archive (VUNA), which has been developed by information specialists for effective management and retrieval of information from newspapers. This article highlights the salient technical issues related to the development of a prototype online digital newspaper information retrieval system suitable for India. The basic architecture, operational features, etc. have been discussed and a comparative picture of respective performance and failures of existing online newspaper archives in India and VUNA also has been drawn. Bangladesh Journal of Library and Information Science Vol.2(1) July 2012 pp.22-38DOI: http://dx.doi.org/10.3329/bjlis.v2i1.12916